FORMING STUDENTS’ CONTENT AND LANGUAGE COMPETENCE IN THE CONDITIONS OF A NON-LINGUISTIC HIGHER EDUCATIONAL INSTITUTION - Sergeeva,; Stanchuliak,; Yulina,; Shishov,; Skaramanga,; Sklyadneva,; Orlova, (Revista Inclusiones, 2019)
Nowadays Russia is almost completely integrated in the global space, which automatically means open competition in all spheres. In order to reach new targets, which are set for the system of professional education by the government, it is necessary to create or to modernize professional educational institutions and processes in them. Accordingly, the Russian higher education school is facing the task of preparing the effective, competitive graduate who meets the requirements of the market economy. The methodological basis of the research comprises the content and language integrated approach, which includes the basics and principles of the integrated teaching of a foreign language and professional disciplines, the socio-constructive approach to teaching foreign languages, and the competence-based approach, which is realized in the Russian higher education school.